METHOD OF CONTRAST IN DESIGNING OF INTERIOR UNITS - Markova, Kremena; Dovramadjiev, Tihomir (Innovation in Woodworking Industry and Engineering design, 2017)
Contrast is a basic method in compositional shape forming. Its invariants, such as the materialistic contrast (between organic and synthetic), contextual contrast, dimensional, plastic, sensory contrast, etc., make the creation of a valuable designer and cultural product possible. The paper presents samples of classic designer furniture and modern innovations to prove the thesis that the method of contrast has the power to bond the physical features of a product to the emotional contact between it and its user, and thereby to unveil successfully the product properties.